Association between weight gain during adjuvant chemotherapy for early‐stage breast cancer and survival outcomes. (10th October 2017) - Schvartsman, Gustavo; Gutierrez‐Barrera, Angelica M.; Song, Juhee; Ueno, Naoto T.; Peterson, Susan K.; Arun, Banu
Abstract: Obese and overweight women have an increased risk of breast cancer and worse outcomes at the time of diagnosis. Women tend to gain weight after breast cancer diagnosis and during chemotherapy for early‐stage disease, which may in turn increase risk for worse outcomes. We examined if weight gained during adjuvant chemotherapy was associated with worse survival outcomes. We queried our database for data on patients who received adjuvant third‐generation chemotherapy for early‐stage breast cancer. Univariate and multivariate analyses by Cox regression were performed for survival outcomes across three categories according to BMI variation from start to end of chemotherapy: >0.5 kg/m 2 loss or gain and stable BMI (±0.5 kg/m 2 ). We included 1998 patients in this study. Women over 50 years old and postmenopausal were more likely to lose weight during adjuvant chemotherapy, whereas women under 30 years old gained more weight ( P  < 0.001). At 1 year postchemotherapy, patients tended to return to their original weight ( ρ  = −0.3, P  <   0.001). On multivariate analysis, BMI increase of >0.5 kg/m 2 compared to maintaining BMI was marginally associated with increased locoregional recurrence risk (HR: 2.53; 95% CI, 1.18–5.45; P  =   0.017), adjusting for grade, stage, and radiation delivery. Weight variation during adjuvant chemotherapy for early‐stage breast cancer may occur as both weight gain and weight loss in a balanced manner. Furthermore, this variation seems to be transient in nature and does not appear to significantly influence recurrence rates and overall survival. Abstract : Weight variation during adjuvant chemotherapy for early stage breast cancer may occur as both weight gain and weight loss in a balanced manner. Furthermore, this variation seems to be transient in nature and does not appear to significantly influence recurrence rates and overall survival.